Rancang Bangun Aplikasi Sistem Pendukung Keputusan Penentuan Pemasok Menggunakan Metode Analytical Hierarchy Process pada PT.Putera Rackindo Sejahtera - Indah widoretno purnomo; A B Tjandrarini; Nunuk Wahyuningtyas (Jurnal Sistem Informasi Universitas Dinamika, 2017)
PT. Putera Rachindo Sejahtera is a company that produces furniture with different raw material needs as customer. the company currently has a thousand suppliers from home and abroad to meet the raw material needs. The process of selecting a supplier for raw materials using criteria such as quality, price, distance, conformity delivery, and delivery time. So it takes a long time to choose the supplier of more than one thousand suppliers that exist .To help companies shorten time supplier selection, made a decision support system application supplier determination using the method of Analytical Hierarchy Process (AHP). Steps being performed on the system that determines the criteria and sub-criteria. Then determine the weight of test criteria and consistency, followed by determining the range of values and weighted sub-criteria. The system generates a priority assessment of suppliers eigen vector calculation criteria with sub criteria. based eigen vector application is made and a series of trials that have been done, the application can generate reports on a supplier of raw materials. Recommendations given supplier is a supplier with the highest ranking three parts purchasing to aid in decision making.